Letters to Oma : A Young German Girl's Account of Her First Year in Texas, 1847 - Gurasich, Marj (Book collections on Project MUSE., 1989)
After her family moves from Germany to Texas in 1847, fifteen-year-old Tina chronicles in letters to her grandmother their struggle to survive in a strange new place while preserving their traditional German ways.